The dimension of Employer Branding and Employee Value Proposition at Academic Community Perspetive - Annisa Ciptagustia; Kusnendi Kusnendi (The International Journal of Business Review (The Jobs Review), 2022)
This study aims to exploration factor of employer branding and employee value proposition for employee of university. Based on previous research all the indicators of employer branding and employee values proposition from potential and existing employee from profit organization, that the reason for this research find indicators from academic sector. This study aims to exploration factor of employer branding and employee value proposition for employee of university. This research conducting at Universitas Pendidikan Indonesia with 50 lecture and 50 employees as source of data with questionnaire and using Explanatory Factor Analysis (EFA). Dimension of Employer branding adopted from Tanwar and Prasad (2017) and Corporate Executive Board (2007) for Employee Value Proposition. Based on the EFA analysis, a classification of new factors/dimensions employer branding was obtained, namely training and development, organizational value/culture, social value, working environment, compensation, and benefits with 21 item scale. For employee value proposition find a classification of new factors / dimensions was obtained, namely work, learning organization, reward, organizational climate, organizational culture, company dimensions, career opportunities, environmental ethics. All the item scale of variable can prediction about university attractiveness from their employee, its implication to university policy to increase engagement their employee.